Finding Ways to Improve Employee Performance in Banking Sector - Ahyar Yuniawan; Eldes Willy Filatrovi; Khoirul Attiq (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2020)
The purpose of this research is to investigate the effects of individual characteristics andIntrinsic motivation on innovative behaviour and employee performance, and the effectinnovative behaviour on employee performance. The study was conducted at banking company, the sample size is about 200 employees. Methods of data analysis used in thisstudy is a quantitative analysis method where quantitative data analysis method is a method of analysis in the form of figures and calculations using statistical methods. In simplify the analysis process, will be used Structural Equations Modeling (SEM). According to the analysis, it is concluded as the followings: individual characteristics has a positive effect oninnovative behaviour; intrinsic motivation has a positive effect on innovative behaviour; individual characteristics has a positive effect on employee performance intrinsic motivation has a negative effect on employee performance and innovative behaviour has apositive effect on employee performance. The results of this study and the limitations found to be a source of ideas and input for the development of this study in the future, the suggested expansion of this research include: Future research is not only done from one employee's perspective, rather it is recommended at the same time from two points of view, namely the perspective of the leaders / top management / manager and also the point of view of the employees themselves.